A new method to measure and model dynamic oxygen microdistributions in moving biofilms. (October 2017) - Wang, Jian-Hui; Chen, You-Peng; Dong, Yang; Wang, Xi-Xi; Guo, Jin-Song; Shen, Yu; Yan, Peng; Ma, Teng-Fei; Sun, Xiu-Qian; Fang, Fang; Wang, Jing
Abstract: Biofilms in natural environments offer a superior solution to mitigate water pollution. Artificially intensified biofilm reactors represented by rotating biological contactors (RBCs) are widely applied and studied. Understanding the oxygen transfer process in biofilms is an important aspect of these studies, and describing this process in moving biofilms (such as biofilms in RBCs) is a particular challenge. Oxygen transfer in RBCs behaves differently than in other biological reactors due to the special oxygen supply mode that results from alternate exposure of the biofilm to wastewater and air. The study of oxygen transfer in biofilms is indispensable for understanding biodegradation in RBCs. However, the mechanisms are still not well known due to a lack of effective tools to dynamically analyze oxygen diffusion, reaction, and microdistribution in biofilms. A new experimental device, the Oxygen Transfer Modeling Device (OTMD), was designed and manufactured for this purpose, and a mathematical model was developed to model oxygen transfer in biofilm produced by an RBC. This device allowed the simulation of the local environment around the biofilm during normal RBC operation, and oxygen concentrations varying with time and depth in biofilm were measured using an oxygen microelectrode. The experimental data conformed well to the model description, indicating that the OTMD and the model were stable and reliable. Moreover, the OTMD offered a flexible approach to study the impact of a single-factor on oxygen transfer in moving biofilms. In situ environment of biofilm in an RBC was simulated, and dynamic oxygen microdistributions in the biofilm were measured and well fitted to the built model description. Graphical abstract: Highlights: In situ environment of biofilm in RBCs was simulated while biofilm was kept static. Oxygen concentrations in biofilm produced by an RBC were dynamically measured. The measured oxygen concentrations were well fitted to the built model description.